Dari Block Grant ke Specific Grant: Konsekuensi Tata Kelola PMK 212 dalam Perencanaan Anggaran Daerah - Tiaramurti, Galuh; Clarisa, Ananda Haya (Lembaga Penelitian Universitas YARSI, 2025)
This study examines the implementation and impact of Ministry of Finance Regulation No. 212/PMK.07/2022 on the 2023 Regional Budget (APBD) formulation in Madiun City. The regulation restructures the General Allocation Fund (DAU) from a block grant to a conditional grant with specific allocations for education, health, infrastructure, PPPK salaries, and urban village funding. This change disrupted the original APBD draft, prepared in January 2022, and required revisions to comply with the new rules. Previously, the DAU was a flexible block grant, budgeted based on the previous year. PMK 212 replaced the earlier regulation that only addressed suspension and reduction of transfer funds, introducing stricter use guidelines. The study employs a qualitative descriptive method through interviews with BKAD officials and analysis of financial documents. Findings show that the regulation reduced budget flexibility, increased administrative burdens, and limited local fiscal autonomy, but improved transparency, accountability, and alignment with national priorities. BKAD responded by issuing internal guidelines and restructuring planning processes. The study concludes that while PMK 212 strengthens fiscal discipline, it diminishes responsiveness to local needs. The managerial implication is the need for improved technical coordination and adaptive planning to address conditional funding constraints in future budgets.